Harmonization of Legislative Efforts for Protection of Critical Infrastructure Within the European Union and Potential Effects for Candidate Countries - GJurovski, Marjan; Poposka, Vesna; Alcheski, Gjorgi (University in Belgrade, 2023)
Crical infrastructure and crical enes, as providers of basic services, play an indispensable role in maintaining vital social funcons or economic acvies in the internal market in the union's increasingly interdependent economy. It is therefore essenal to establish a Framework of the Union in order to simultaneously strengthen the resilience of crical enes in the internal market by establishing harmonized minimum rules and assistance with the help of coherent and dedicated support and surveillance measures. Those processes already started occurring , facing growing and connuous threats of today’s world. Direcve (EU) 2022/2557 Ͳ formally adopted by the coͲlegislators on 14 December 2022, introducing a number of addional crical infrastructure protecƟon (CIP) measures and replacing Council Direcve 2008/114/EC Ͳ also known as ECI Direcve, is supposed to be transposed into naƟonal legislaons of EU memberstatesin the upcoming two years. In parallel, update of NIS direcves came in power as many diīerent sector related legal documents. For the candidate countries, it is addional eīort of essenal meaning, especially for North Macedonia that is a NATO member. This paper aims to provide an orientaƟon framework toward the key achievementsthat are supposed to be met for eīecve protecon of crical infrastructure at naonal level
Keywords: crical infrastructure, enes, harmonizaon, legislaon.